(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The study examined teachers’ roles in the implementation of inclusive education practices in the Central Region of Ghana. Qualitative case study design and multistage sampling technique were employed for the study. Semi-structured interview guide was used to gather data. Twenty-four teachers in twelve schools were interviewed. The findings revealed that some teachers varied their teaching methods and strategies to enable all learners have equal access to the curriculum. It was found that teachers had significant role to play in community sensitisation programme to educate the public on how learners with special educational needs would be accepted in the society. However, most teachers did not have much knowledge on how to screen and/or refer at risk learners for further evaluation to determine their real needs. Extensive in-service training must be offered by special education experts to enable teachers perform effectively in the practice of inclusive education.